THE CORRELATION OF BIRTH WEIGHT WITH INCIDENCE OF RUPTURE PERINEUM AT PRIVATE PRACTICE OF MIDWIVES IN EAST JAKARTA - Okta Zenita Siti Fatimah; Dewi Suri Damayanti; Seventina Nurul Hidayah (Siklus : Journal Research Midwifery Politeknik Tegal, 2021)
In the process of spontaneous delivery, there was a risk of bleeding due to perineal rupture. The perineal rupture that did not handle properly would increase the risk of infection. The purpose of the study was to determine the relationship between perineal rupture with newborn birth weight. The research method used a cross-sectional quantitative method. In this study, the population was mothers who gave birth in January-September 2020 in the private practice of midwives in East Jakarta and obtained 389 people. The number of respondents in this study was 169 respondents. Data collection used primary data by filling out a google form. Collected data analyzed using univariate and bivariate analysis (Chi-Square test). This study showed that respondents who experienced perineal rupture during delivery were 94.7%, and 94.1% of them gave birth to average baby birth weight. The results of statistical tests with chi-square obtained a p-value of 0.081 which means there is no significant relationship between newborn weight and perineal rupture. Recommendations for health workers, especially midwives, need to increase their knowledge and skills through training and health seminars, especially on preventing perineal rupture during childbirth and applying perineal massage techniques following standard operating procedures to provide counseling and training. Further research needs to be carried out to analyze the incidence of perineal rupture during delivery to reduce the incidence of perineal rupture.Keywords: perineal rupture, birth weigth